2013
DOI: 10.1186/1471-2407-13-487
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to treatment guidelines and survival in triple-negative breast cancer: a retrospective multi-center cohort study with 9156 patients

Abstract: BackgroundTriple-negative breast cancer (TNBC) remains a challenging topic for clinical oncologists. This study sought to evaluate TNBC versus other breast cancer subtypes with respect to survival parameters. We evaluated possible differences in survival in TNBC by age and by the extent to which evidence-based treatment guidelines were adhered.MethodsThis German retrospective multi-center cohort study included 9156 patients with primary breast cancer recruited from 1992 to 2008.ResultsThe rates of guideline ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 23 publications
2
40
2
Order By: Relevance
“…A total of 11,982 breast cancer patients were recruited at the University Medical Centers Mainz and Ulm as well as 16 associated Ulm network clinics [10,11]. Women were eligible for participation in the study if they were diagnosed with primary breast cancer between 1998 and 2008 with no metastases at the time of diagnosis and had undergone breast surgery.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 11,982 breast cancer patients were recruited at the University Medical Centers Mainz and Ulm as well as 16 associated Ulm network clinics [10,11]. Women were eligible for participation in the study if they were diagnosed with primary breast cancer between 1998 and 2008 with no metastases at the time of diagnosis and had undergone breast surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has demonstrated that certain groups of patients are less likely to receive guideline-concordant care for cancer, ie, they are more likely to underuse medical services. [8][9][10][11] Data on factors influencing overused, low-value medical services are limited. Inappropriate imaging of early breast and prostate cancers was driven primarily by regional differences rather than by patient factors in one study, suggesting provider or system influence on concordance with imaging recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…This recommendation matches with those from the AGO but points out essential and important aspects for young patients in more detail [8]. The BRENDA trial - a German retrospective multi-center cohort study including 9,156 patients with primary breast cancer recruited from 1992 to 2008 - examined the influence of therapy in adherence to guidelines (following the German S3 guideline) on RS and OS, and showed that guideline-consistent therapy improves RS and OS [9,10]. To determine whether young patients in Germany were treated in accordance with applicable AGO guidelines, we evaluated the data of 1,053 women who participated in an in-patient rehabilitation mother-child program in Germany between 2007 and 2011 and, further, compared the treatment of young mothers with data of the OVIS (oncological treatment of tumor patients in Schleswig-Holstein) study, a mixed-age collective.…”
Section: Introductionmentioning
confidence: 54%
“…Therefore, the treating physician has to weigh the benefits of therapy against the potential harms, keeping in mind the goal of maximum long-term benefit with minimum long-term toxicity. Therapy in accordance with the guidelines improves RS and OS [2,9,10], and should therefore be performed if possible. As presented at the Combating Breast Cancer Conference 2013, a continuous reduction of mortality in breast cancer has been observed over the past few years in Germany.…”
Section: Discussionmentioning
confidence: 99%